Effect of B2O3 on ESR Slag Viscosity for Remelting 9CrMoCoB Steel - Liu, Fu-bin; Li, Hua-bing; Zhen, Peng-lei; Tao, Xue-ru; Jiang, Zhou-hua; Geng, Xin (ISIJ International, 2022)
The viscosity of the slag constituted by 55%CaF2–20%CaO–3%MgO–22%Al2O3–x%B2O3 (mass fraction: x ≤ 3) was measured by rotating cylinder method during the electroslag remelting (ESR) of 9CrMoCoB steel to analyze the effects of the B2O3 content on slag viscosity, break point temperature, and activation energy for viscous flow. Meanwhile, the slag’s structural characteristics were studied by Raman spectrometry. Results indicated that when T ≥ 1663 K, the viscosity changed gently with temperature, showing the value of about 0.055 Pa·s, which was rarely affected by w(B2O3). However, with the increase of w(B2O3) in the slag, the Ca3B2O6 with a low melting point was formed, reducing the slag’s break point temperature from 1628 K to 1563 K. According to the NBO/T value and Raman spectra, B2O3, as a network generating oxide, improved the slag’s degree of polymerization, thus strengthening and complicating its network structure at high temperatures. In addition, as the w(B2O3) increased from 0 to 3%, the activation energy for viscous flow rose from 64 kJ·mol−1 to 94 kJ·mol−1 in the slag.